"Three‐in‐One" Multi‐Level Design of MoS2‐Based Anodes for Enhanced Sodium Storage: from Atomic to Macroscopic Level. (5th January 2022) - Sui, Simi; Xie, Haonan; Liang, Ming; Chen, Bochao; Liu, Chunyang; Liu, Enzuo; Chen, Biao; Ma, Liying; Sha, Junwei; Zhao, Naiqin
Abstract: Constructing sodium‐ion battery anodes with efficient ion/electron transport and high cycling stability is significantly promising for applications but still remains challenging. Here, "three‐in‐one" multi‐level design is performed to develop a carbon‐coated phosphorous‐doped MoS2 anchored on carbon nanotube paper (P‐MoS2 @C/CNTP). The Na + diffusion and electron transport, as well as the structural stability of the whole anode are simultaneously enhanced through the synergistically optimization of P‐MoS2 @C/CNTP at atomic, nanoscopic, and macroscopic levels. Resulted from the multi‐level modification, the synergetic mechanism has been demonstrated by electrochemical measurement and theoretical calculation. As a result, the free‐standing P‐MoS2 @C/CNTP anode presents a high rate performance (150 mA h g −1 at 5 A g −1 ) and a long cycling life (1 A g −1, 1200 cycles, 249 mA h g −1 ). This work provides a new approach to the design and fabrication of high‐performance conversion‐type electrode materials for rechargeable batteries application. Abstract : By "three‐in‐one" multi‐level optimization on atomic, nanoscopic, and macroscopic structures, carbon‐coated phosphorous‐doped MoS2 anchored on CNT paper (P‐MoS2 @C/CNTP) are designed and prepared. The unique P‐MoS2 @C/CNTP exhibits synergetic enhancement on Na + diffusion, electron transport, and structural stability in the whole anode, resulting in enhanced sodium storage capability.